Effect of nanosized phthalocyanine on the photovoltaic performance of titanium oxide/metal organic framework composite - Ramaripa, Phuti Suzan (My University, 2023)
This thesis reports on the dye sensitized solar cell (DSSC), an unconventional opportunity for silicon solar cell owing to their flexibility, transparency and low cost. DSSC is one of the electrical production technology, which uses the photovoltaic effect. The necessity for DSSC to captivate more of the sunlight radiation was the motive force for the fabrication of semiconductor materials based on their high surface area. The main components in DSSC are the conducting substrate, dye, photoanode, catalyst and electrolyte. The photoanode is well known as an element that generates the energy conversion efficiency. There are different photoanode materials that were studied to date. Amongst photoanode materials, titanium dioxide (TiO2) materials are extensively documented, explored and considered. In this work, efforts are made to survey the strategies to advance the energy efficiency of TiO2 based photoanode with introduction of metal organic framework (MOF) in DSSC to suppress the recombination rate and electron loss. It was observed that to attain a high conversion yield in DSSC, it is vital to collect the produced ion carriers before electron re-combination. This work is devoted to the TiO2 and MOF photoanode, their properties and various improvement approaches using nanosized phthalocyanine for photovoltaic performance. A high surface area MOF was incorporated into TiO2 network to form a TiO2-MOF composite using sol–gel method and was employed as a photoanode material for photovoltaic applications. X-ray Diffraction patterns (XRD), Fourier Transform Infrared (FTIR), thermal gravimetric analysis (TGA), differential thermal analysis (DTA) and Raman analyses showed the presence of MOF clusters in the TiO2 aerogel network. The scanning electron microscopic (SEM) images revealed the smooth irregular shape of TiO2, octahedral shape of MOF and continuous arrangement of pore-solid network structure for composite. The TiO2-MOF composite showed a Brunauer, Emmett and Teller (BET) surface area of 111.10 m2g−1 as compared to the surface area of TiO2 (262.90 m2 g−1) and MOF (464.76 m2g-1). It was seen that an increase in average pore size of 3.40 nm for composite analogous with the pore size of TiO2 (2.66 nm) and MOF (2.56 nm). Cyclic voltammetry (CV), electectrochemical impedance spectroscopy (EIS), and chronoamperometric were used to determine the energy level and suggesting a fast electron transfer as well as the high ionic conductivity. The overall power conversion efficiency of 0.722% along with a photocurrent density 0.46 mAcm−2 was achieved by TiO2-MOF composite. The other objective was to incorporate of phthalocyanine dye into TiO2-MOF composite to enhance the photovoltaic performance of DSSCs. The structural and morphological studies of the prepared CuPc dye and TiO2-MOF after dye adsorption were characterized with various analytical techniques. The ultraviolet visible (UV-vis) spectrum of CuPc showed absorption bands at 370 nm and 798 nm, which are attributable to the B-band or Soret band and the Q-band in H2SO4 solvent. The optical studies revealed the absorption of CuPc by TiO2-MOF composite. The XRD patterns have shown the anatase TiO2 phases, MOF and CuPc phases in the TiO2-MOF after dye adsorption (TiO2-MOF/CuPc). Raman and FTIR spectroscopies have shown the N-Cu-N and O-Cu-O vibrational mode for both MOF and CuPc, N-Cu-N vibrational mode on CuPc, as well as the symmetrical and antisymmetric vibration mode O-Ti-O of TiO2 in TiO2-MOF/CuPc. BET have revealed the decrease in surface area after CuPc adsorption in the composite. The SEM images of the final TiO2-MOF/CuPc revealed the rod structure of CuPc, agglomerated structure of TiO2 upon the introduction of MOF and the octahedral structure of Cu-MOF. The Tauc plot of TiO2-MOF/CuPc, has shown that there are differences in band gabs of the materials. The band gab of the final composite is 2.7 eV eV. A maximum photocurrent and power efficiency of 1.80 mA cm−2 and 1.63% at 0.8 V were recorded for TiO2-MOF/CuPc composite under simulated light source, respectively. Furthermore, Copper phthalocyanine derivative, copper phthalocyaninine nanowire dye was synthesized from copper phthalocyanine molecule. This material was responsible for the dye material in the DSSCs technology. Copper phthalocyanine nanowire (CuPcNW) dyes are employed in DSSCs to generate low-cost devices, light-harvesting, fast electron transfer material, and prevent recombination process, as well as conductivity improvement. In this study, investigation for the effect of CuPcNW dye on TiO2, MOF, and TiO2-MOF in photovoltaic performance were made. Electrochemical characterizations such as CV and EIS were used to determine the highest occupied molecular orbital (EHOMO) and lowest unoccupied molecular orbital (ELUMO) energies as well as the ionic conductivity. The EHOMO and ELUMO values were found to be -5.1 and -4.31 eV in the TiO2-MOF/CuPcNW ternary nanocomposite, respectively. The EIS behaviour showed the improved conductivity of the ternary nanocomposite with a value of 244 μS/cm. It was seen that the TiO2-MOF/CuPcNW ternary nanocomposite achieved a maximum power conversion efficiency of 6.467% at lower potential of 0.43 V owing to the presence of CuPcNW, which improved the photocurrent density. The impact of copper phthalocyanine nanotube (CuPcNT) dyes on performance of TiO2-MOF nanocomposite in the performance of photovoltaicapplications was investigated. The CuPcNW was hydrothermally treated at 180 °C in order to produce a self-assemble rectangular CuPcNT. This material was introduced as dye for DSSCs into TiO2-MOF composite to form TiO2-MOF/CuPcNT ternary nanocomposite. The UV-vis revealed the smaller band gap of 2.62 eV, and absorbed at the region beyond the UV light with the wavelength of 798 nm. The x-ray diffraction patterns showed the TiO2, MOF and CuPcNT phases, and functional groups in the TiO2-MOF/CuPcNT nanocomposite. The CV showed the half wave peak potentials of the TiO2-MOF/CuPcNT ternary nanocomposite with the values of 0.38 and 0.10 V for the oxidation and reduction reversible reactions with the calculated HOMO and LUMO energies of -4.85 and -4.37 eV, respectively. The EIS for TiO2-MOF/CuPcNT ternary nanocomposite revealed lower conductivity of 1.39 μS/cm with a lifetime of 1.94 ms as compared to the TiO2-MOF/CuPcNW material. Interestedly, the maximum photocurrent and power conversion efficiency of the TiO2-MOF/CuPcNT ternary nanocomposite were 7.02 mA cm-2 and 11.69 % at lower potential of 0.35 V under a simulated light source higher than in the TiO2, TiO2-MOF, TiO2-MOF/CuPc, and TiO2-MOF/CuPcNW. In conclusion, the role of nanosized pthalocyanine dyes may be used to improve photovoltaic performance of TiO2-MOF composite and make the resultant composites to be excellent candidates for dye-sensitized solar cell applications.
Thesis (Ph.D.(Chemistry)) -- University of Limpopo, 2023
Keywords: Nanocomposite; Nanosized phathalocyanine; Oxide/ metal organic framework; Titanium dioxide; Phthalocyanines; Nanocomposites (Materials); Photovoltaic cells; Solar cell; Silicon solar cells